Sub-regional 'other-accent' effects on lay listeners' speaker identification abilities: a voice line-up study with speakers and listeners from the North East of England. (16th November 2018) - Braun, Almut; Llamas, Carmen; Watt, Dominic; French, Peter; Robertson, Duncan
Abstract : Previous studies have shown that listeners perform worse in speaker identification experiments when they are unfamiliar with the accents of the speakers. Such effects have been documented for listeners hearing unfamiliar foreign languages (language familiarity effect) and unfamiliar regional accents ('other-accent' effect). The present study investigates the 'other-accent' effect at a sub-regional level. Listeners from three different localities (Newcastle, Sunderland and Middlesbrough) within the same greater dialectal region (the North East of England) participated in one of three target-present voice line-ups using samples spoken by speakers from one of the three localities. Listeners who heard a voice line-up in their own local accent (ingroup listeners) missed the target speaker's voice significantly less often than listeners who heard a voice line-up comprised of speakers of one of the other two local accents (out-group listeners). The proportions of correct hits and false alarms were approximately similar across in-group and out-group listeners.